The role of drawing in childrens' imagination / Nor Shakir Nordin - Nordin, Nor Shakir (2013)
The purpose of this study is to identity the usage of Drawing on Imagination among Young Children in one primary school in Terengganu. This study covers the stages of children imagination based on their drawing development and how young children created simple drawing trough imagination. Twelve students that were picked randomly from the school that have been chosen in Terengganu are participated. The samples of this study are students drawing from eight years old. During the research, twelve drawing were collected and analyzed. In this study, the observations according to the six stages of artistic development from Victor Lowenfeld were used. Results of the study, art is one of best ways to build intelligence. The children had developed and recorded a complex narrative of what they can see, modify, elaborate and talk about while drawing from imagination.